Kesehatan Mental Remaja: Mengatasi Stigma dan Membangun Kesadaran - Hidayah, Miftahul (Maliki Interdisciplinary Journal, 2025)
Adolescent mental health is a crucial issue that is gaining increasing attention from society. Despite the growing awareness of the importance of mental health, the stigma surrounding individuals with mental health issues often hinders their efforts to seek help. Various forms of stigma faced by adolescents can obstruct communication and the support they need. Appropriate education can help reduce stigma, encouraging adolescents to speak about their problems and seek the necessary support. Therefore, it is essential for educational institutions to implement effective mental health awareness programs. Stigma is a major barrier to addressing adolescent mental health issues, often stemming from a lack of knowledge and understanding within the community. Training for parents and teachers is needed to help them recognize the signs of mental health issues and provide appropriate support. Public awareness campaigns should also be conducted regularly to educate the public and reduce the stigma that prevents adolescents from seeking help.